Efficacy of plum blossom acupuncture on alopecia areata – A case report - Thanudhas, Sujithra Sreekumari (Indian Journal of Case Reports, 2021)
Alopecia areata (AA) is a complex autoimmune condition that causes non-scarring hair loss and may present at any age. It typically presents with sharply demarcated round patches of hair loss. AA presents heterogeneously and is influenced by both environmental and genetic factors. There is no effective pharmacological treatment currently available for this disorder so far. We had an opportunity to treat a patient with AA using acupuncture. The patient was a 23-year-old male who presented to us with a complaint of sudden hair loss in patches in two demarcated round areas in a diameter of 2–3 cm on the back of the head for the past year. He was diagnosed as AA by AA progression index. After a long treatment course of about 3 months with acupuncture, this patient showed significant hair growth.